2016
DOI: 10.5007/1980-0037.2016v18n6p658
|View full text |Cite
|
Sign up to set email alerts
|

Projeto Esporte Brasil: perfil da aptidão física relacionada ao desempenho esportivo de crianças e adolescentes

Abstract: -The aim of this study was to outline the physical fitness profile related to sport performance of Brazilian children and adolescents, stratified by sex. This is a descriptive cross-sectional study and information was obtained from the Projeto Esporte Brasil (PROESP-Br). The sample consisted of 8,750 voluntary subjects aged 7-17 years evaluated in the period between 2013 and 2015. The following variables were evaluated: lower limb strength (LLS) through the horizontal jump test and upper limb strength (ULS) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 16 publications
0
26
1
5
Order By: Relevance
“…Regarding the location of these studies, it was identified that the Southern and Southeastern regions of Brazil were those that most published articles on MS in children and adolescents, with 18 studies 7-9,12-27 . Regarding the design of included studies, 22 had cross-sectional 3,7-9,14-21, [23][24][25][27][28][29][30][31][32][33][34][35] and five longitudinal design 12,13,22,26,36 (Table 1). The studies covered different primary goals as can be observed in Table 1; however, all of them performed MS measurements as defined in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Regarding the location of these studies, it was identified that the Southern and Southeastern regions of Brazil were those that most published articles on MS in children and adolescents, with 18 studies 7-9,12-27 . Regarding the design of included studies, 22 had cross-sectional 3,7-9,14-21, [23][24][25][27][28][29][30][31][32][33][34][35] and five longitudinal design 12,13,22,26,36 (Table 1). The studies covered different primary goals as can be observed in Table 1; however, all of them performed MS measurements as defined in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Freitas et al, 35 Montes Claros, MG No study was classified with low methodological quality / high risk of bias. Moderate methodological quality/moderate risk of bias was verified in ten studies (37.0%) 7,12,13,15,19,21,23,26,28,29 , while seventeen studies … continue (67.0%) 3,8,9,14,16,17,20,22,24,25,27,[30][31][32][33]35,36 were classified with high methodological quality / low risk of bias (Table 2). MS was investigated in fourteen different ways.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations